Double standards in the accumulation and utilisation of ‘aesthetic capital’ - Outi Sarpila; Aki Koivula; Iida Kukkonen; Erica Åberg; Tero Pajunen (Elsevier BV, 2025)
Physical appearance as a form of capital has received increasing attention in sociology in recent years. The logic suggests that ‘aesthetic capital’, like other forms of capital, can be accumulated and utilised in economic and social exchange. However, previous research has not paid attention to societal norms that may regulate the accumulation and utilisation of ‘aesthetic capital’ differently for men and women. In this paper, we turn our attention to such gendered norms, that is, double standards, by analysing unique measures for both accumulation and utilisation based on a split-ballot survey design. Our study shows that there are double standards in certain norms regarding the accumulation and utilisation of ‘aesthetic capital’. This indicates the existence of double standards is context dependent. A double standard in accumulation means more approval of women's behaviour, whereas a double standard in utilisation implies more disapproval of women's conduct. We conclude that ‘aesthetic capital’ can be seen as not so much something that individuals accumulate and utilise but as something that context-dependent gendered norms regulate.